Marketing Optimization in Higher Education: Increasing Student Satisfaction through Social Media with Student and Lecturer Involvement - Sheila Belladiena (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
This research aims to analyze marketing in higher education by considering the independent variables interactivity with peers, interactivity with lecturers, active collaborative learning. Meanwhile, the dependent variables studied involve the variables engagement, social media use, student satisfaction. 157 research respondents were involved in this research. Data processing is carried out using the SmartPLS method. As a result, this research shows that all indicators in the dependent and independent variables produce positive and valid values. These findings contribute to a deeper understanding of the dynamics of marketing in higher education, particularly in the context of interactivity, active collaborative learning and the use of social media, all of which have the potential to increase student satisfaction. This study contributes to enriching the marketing literature in higher education.